Ibn Miskawaih’s Religious-Rational Thought on the Philosophy of Moral Education and Its Relevance to Contemporary Islamic Education: Pemikiran Religius-Rasional Ibnu Miskawaih tentang Filsafat Pendidikan Akhlak dan Relevansinya bagi Pendidikan Islam Kontemporer - Sarmiati, Eni; Siregar, Maragustam (SiRad: Pelita Wawasan, 2025)
Moral education plays a significant role in the field of education. Ibn Miskawaih, a Muslim philosopher who concentrated on ethical philosophy, provided an essential foundation for moral development. This article explores Ibn Miskawaih’s biography and works, his thoughts on the philosophy of moral education, and their relevance to contemporary Islamic education. This study employs a qualitative approach using library research. The primary source is the translated version of Ibn Miskawaih’s Tahdzib al-Akhlaq, while secondary sources include relevant books and scholarly journals. Data were collected through documentation and analyzed using inductive methods. Ibn Miskawaih argued that the essence of human goodness lies in the ability to think, which distinguishes humans from other creatures. The main goal of moral education is to elevate humans from a despicable state to noble character. The proposed methods include habituating students to love religious values, perform religious obligations, control worldly desires, and develop social awareness. Ibn Miskawaih also permitted light punishment as a means of discipline. His thoughts remain relevant to modern education, though their application in Indonesia faces dilemmas due to the provisions of Law No. 23 of 2002 on Child Protection. [Pendidikan akhlak memiliki peranan penting dalam dunia pendidikan. Ibnu Miskawaih, seorang filsuf Muslim yang berfokus pada filsafat etika, telah meletakkan dasar dalam proses pembinaan akhlak. Artikel ini menguraikan biografi singkat dan karya-karya Ibnu Miskawaih, pemikirannya mengenai filsafat pendidikan akhlak, serta relevansinya dengan pendidikan Islam kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka (library research). Sumber primer penelitian adalah terjemahan kitab Tahdzib al-Akhlaq karya Ibnu Miskawaih, sedangkan sumber sekunder diperoleh dari buku dan jurnal ilmiah terkait. Data dikumpulkan melalui metode dokumentasi dan dianalisis dengan teknik induktif. Menurut Ibnu Miskawaih, esensi kebaikan manusia terletak pada kemampuannya berpikir, karena berpikir merupakan ciri khas manusia yang membedakannya dari makhluk lain. Tujuan utama pendidikan akhlak adalah mengangkat manusia dari derajat tercela menuju kesempurnaan akhlak. Metode yang diajukan meliputi: membiasakan murid mencintai kemuliaan agama, melaksanakan kewajiban syariat, mengendalikan hawa nafsu duniawi, serta menumbuhkan kepedulian sosial. Ibnu Miskawaih juga memperbolehkan bentuk hukuman ringan sebagai sarana mendisiplinkan murid. Pemikirannya tetap relevan dengan dunia pendidikan kontemporer, meskipun penerapannya di Indonesia menghadapi dilema akibat benturan dengan Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak.]